Особенности ламинарного течения в секториальном диффузоре с переменной шириной вдоль канала - Ульев, Леонид Михайлович (НТУ "ХПИ", 2004)
The problem of laminar flow in the sector diffuser with variable width along the channel was solved in this paper. Expressions for pressure drop and velocity distribution in the channel were received. The comparison between solution which was received in sector diffuser and for coaxial conic diffuser was performed. The parameters for the largest deviation in the solutions were obtained. The results are used for calculation of molding equipments
Keywords: перепад безразмерного давления; сечение канала; диффузорное течение жидкости; площадь поверхности